An Overview of Systematic Reviews of Moxibustion for Knee Osteoarthritis - Yin, Shao; Zhu, Fengya; Li, Zhao; Che, Deya; Li, Liuying; Feng, Jie; Zhang, Lu; Huo, Zhenyi (Frontiers in Physiology, 2022)
Background Currently, many systematic reviews (SRs) of moxibustion as a treatment of KOA have been published. However, the evidence of different SRs of moxibustion to treat KOA has not been comprehensively evaluated. Aim This overview aimed to evaluate the existing results and provide scientific evidence of the effectiveness and safety of moxibustion in the treatment of KOA. Methods We conducted a comprehensive search of Embase, PubMed, Web of Science, Cochrane Library, SinoMed, CNKI, Wanfang, VIP, and other databases until October 31, 2021. A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2) was used to assess the methodological quality of SRs. Preferred Reporting Item for Systematic Reviews and Meta-Analyses was used to evaluate the reporting quality, and the risk of bias in SRs was evaluated by ROBIS Tool. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool to determine the strength of evidence and conducted a meta-analysis of the total effectiveness rate. Results Finally, 10 qualified SRs were included, including 57 randomized controlled trials and 5,149 participants. All SRs evaluated by AMASTAR-2 had more than one critical deficiency, so all SRs were rated as critically low. In the PRISMA checklist, the manuscript structures of the included SRs were relatively complete. Including four SRs with a low risk of bias and six with a high risk of bias using the ROBIS tool. In GRADE, two items (6.25%) were rated as high quality, three (9.37%) as medium quality, 17 (53.12%) as low quality and 10 (31.25%) as very low quality. A re-meta-analysis showed that moxibustion and moxibustion combined treatment improved the total effectiveness rate in knee osteoarthritis (risk ratio = 1.17, 95% confidence interval 1.13–1.21, P < 0.001 and risk ratio = 1.13, 95% CI: 1.04–1.23, P < 0.001), with low heterogeneity (I2 = 36.3%, P = 0.020, and I2 = 0.0%, P = 0.956). A total of eight SRs reported adverse events, and no serious adverse events occurred in the moxibustion group and control group. Conclusion Moxibustion seems to be effective in treating KOA. Four SRs reported 10 common discomfort symptoms caused by moxibustion, and these adverse events can spontaneously subside, even can be avoided, therefore, moxibustion for KOA appears to be safe. However, the reliability of the results is reduced by the high risk of bias of the original studies and the low methodological quality of SRs. Therefore, future studies should pay more attention to the quality of the original study and the evidence quality of the SRs to provide more powerful and scientific evidence of the effectiveness and safety of moxibustion treatment of KOA.